PROBLEMATICS OF BIPA LEARNERS LEARNING CULTURE IN ELECTIVE CLASSES - Galuh Prameswari, Renanda Winar; Muzaki, Helmi; Suyitno, Imam; Susanto, Gatut; Ng, Yufita (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2024)
This research aims to analyze the problems faced by BIPA students in learning culture in elective classes. This research uses qualitative method with descriptive research type. The results of this research show several things that become obstacles for foreign students in learning other cultures, namely the difficulty level of teaching materials, inadequate facilities and infrastructure, and cultural differences.